Teacher's Speech Acts as Interaction in Learning Language Indonesia - Hermansyah, Sam; Natsir, Nuraisa (Global Synthesis in Education Journal, 2023)
The research was conducted with the aim of describing teacher's speeches in Indonesian learning in class when learning Indonesian. The type of this research is qualitative research with descriptive methods. Data collection is done by listening activities. The data that is observed is obtained from stress devices and notes when the research was examined. Teacher's speeches classified by the researchers is divided into three parts, namely utterance when giving lessons, when delivering lessons and lessons that are lessons related. Based on research conducted, it can be concluded that teachers often use assertive requirements and use regional language as the languages of instruction